1982
DOI: 10.1002/path.1711360307
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane and phagosome localisation of the activated NADPH oxidase in elicited peritoneal macrophages of the guinea‐pig

Abstract: The subcellular distribution of the NADPH oxidase of guinea-pig peritoneal-elicited macrophages was investigated. Post-nuclear supernatants obtained from PMA-stimulated macrophages were fractionated in discontinuous sucrose gradients. The NADPH oxidase was found to be enriched at the interface between 20 and 34 per cent sucrose. This interface was also enriched in 5'-nucleotidase, a plasma membrane marker and in glucose-6-phosphatase and NADPH-cytochrome c reductase, two endoplasmic reticulum markers. The dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…This minimalist in vitro experiment verifies sensitivity of the polymersome fluorescence to ROS, but it should be noted that in vivo these shifts in I 550/640 ratio may vary extensively by cell type, activation state, and mechanism of endocytosis due to the dynamic and complex mixtures of ROS present in endosomal compartments. 6, 7, 12-14 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This minimalist in vitro experiment verifies sensitivity of the polymersome fluorescence to ROS, but it should be noted that in vivo these shifts in I 550/640 ratio may vary extensively by cell type, activation state, and mechanism of endocytosis due to the dynamic and complex mixtures of ROS present in endosomal compartments. 6, 7, 12-14 …”
Section: Resultsmentioning
confidence: 99%
“…To carry out these activities, macrophages trigger a respiratory burst during phagocytosis, rapidly generating reactive oxygen species (ROS) mainly at the plasma membrane. 7, 8 Rapid degradation of engulfed materials is further enhanced by massive recruitment of V-ATPase, which acidifies their phagosomes within minutes to activate a host of proteolytic enzymes. 9, 10 DCs on the contrary, demonstrate a more subtle oxidation within their phagosomes over the course of several hours and a lower potency for degradation relative to macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages lack azurophil, specific granules, and secretory vesicles found in neutrophils (18,19). Macrophages also participate actively in the removal of dead cells.…”
Section: Macrophagesmentioning
confidence: 99%
“…After recognition, macrophages engulf their 'prey' into phagosomes, which mature to digestive organelles (phagolysosomes) by interchanging membrane and soluble material with different intracellular compartments. Macrophages lack azurophil, specific granules, and secretory vesicles found in neutrophils (18,19). Consequently, phagosome maturation in macrophages differs in quality and kinetics from that in neutrophils.…”
Section: Macrophagesmentioning
confidence: 99%
“…The localization of NADPH oxidase components in the phagosome membrane was also reported [11]. The localization of the cytosolic components of NADPH oxidase and the mechanisms of their assembly in the phagosome membrane have been extensively studied [12][13][14]. Recently, histochemical determination of 02-generation using DAB/Mn 2+ revealed that the soluble stimulants PMA and fMLP produced 02"-not only on the cell surface but also in intracellular nonphagocytic-vacuoles 115 '16].…”
Section: Introductionmentioning
confidence: 97%